E-Commerce Consumer Satisfaction Analysis: A Study on the Shopee Platform - Endang Dwi Amperawati (Budapest International Research and Critics University, 2022)
In this modern era, people have a desire for something very diverse, and to fulfill this desire Shopee is here to answer existing problems. Basically, customer satisfaction is a sign of the company's success, so it is important and cannot be underestimated. This research was made with the aim of testing the effect of Price, Discount, and Service Quality on E-commerce Consumer Satisfaction on the Shopee Application. The sample method used in this study was obtained by means of a questionnaire, and got 31 respondents from the questionnaire that had been distributed. The analytical method used was multiple linear regression and processed using SPSS. The results showed that only the price and quality of service were positive for shopee application consumer satisfaction.